Environmental benchmarks for the European cement industry - Sambataro, Luciano (2024)
The urgent need to address climate change has pushed Europe to the forefront of environmental legislation initiatives, such as the Environment Action Program (EAP) within the European Green Deal and the disclosure of Environmental Product Declarations (EPDs) in the construction sector. The cement industry plays a vital role in this transition because it is one of the biggest contributors to greenhouse gas emissions worldwide. EPDs have managed to articulate the environmental information flow across different stakeholders, allowing them to incorporate sustainability design practices at the manufacturing, construction, and design levels. However, current EPDs are deterministically disclosed and lack benchmarks, hindering effective comparison and impeding sustainable material development. To address this challenge, the present research introduces a novel Life Cycle Assessment (LCA)-based probabilistic analysis to develop clinker and cement benchmarks. The proposed method incorporates data from industry reports, environmental databases, and EPDs, to generate the stochastic benchmarks. Moreover, a wide range of environmental performance indicators at a national level in Europe are covered, offering a holistic perspective beyond climate change. The results highlight the benefits of using country-specific environmental benchmarks, reducing the standard deviation of results by 2 to 7 times compared to background datasets. The reduction of clinker content proved to reduce 7 to 9 kg CO2eq/t for every 1% reduction in all countries. However, it also increased other indicators depending on the mineral component used as a replacement, underscoring the need for holistic analysis. The research also exposes discrepancies between EPDs and industry-related data, accentuating the need for stochastic information disclosure to enhance reliability and facilitate decision-making by stakeholders. Another significant contribution of this research is the development of an extensive open-access database, providing a reference for future developments regarding sustainable cement and concrete.